Conceptions of Physical Education teachers about Cooperative Games (Research, Society and Development, 2022)
Games are used with pedagogical strategies in many curricular components, in particular, Physical Education teachers. Currently there is a changing trend and competitive games are being adapted to be cooperative. Thus, in this research, the objective was to analyze the conceptions about the cooperative games of the teachers of the curricular component of Physical Education who work in the Integrated High School. The methodology was of a qualitative approach. The data collection instrument was a semi-structured interview and the research participants were Physical Education teachers who work in technical courses integrated to high school. To analyze the data, the content analysis technique was used, in this way, three conceptions of the teachers about the cooperative games were categorized: 1) Skills developed by the games; 2) Cooperative games in Physical Education classes; 3) Socio-emotional education in the curriculum. The participating teachers pointed out the need to include the theme in the integrated high school curriculum, in addition, they stated that they work with cooperative games in their classes, but they need continuing education on the subject.